Mouse papillomavirus type 1 (MmuPV1) DNA is frequently integrated in benign tumors by microhomology-mediated end-joining. - Lulu Yu; Vladimir Majerciak; Xiang-Yang Xue; Aayushi Uberoi; Aayushi Uberoi; Alexei Lobanov; Xiongfong Chen; Maggie Cam; Stephen H Hughes; Paul F Lambert; Zhi-Ming Zheng (PLoS Pathogens)
MmuPV1 is a useful model for studying papillomavirus-induced tumorigenesis. We used RNA-seq to look for chimeric RNAs that map to both MmuPV1 and host genomes. In tumor tissues, a higher proportion of total viral reads were virus-host chimeric junction reads (CJRs) (1.9‰ - 7‰) than in tumor-free tissues (0.6‰ - 1.3‰): most CJRs mapped to the viral E2/E4 region. Although most of the MmuPV1 integration sites were mapped to intergenic regions and introns throughout the mouse genome, integrations were seen more than once in several genes: Malat1, Krt1, Krt10, Fabp5, Pard3, and Grip1; these data were confirmed by rapid amplification of cDNA ends (RACE)-Single Molecule Real-Time (SMRT)-seq or targeted DNA-seq. Microhomology sequences were frequently seen at host-virus DNA junctions. MmuPV1 infection and integration affected the expression of host genes. We found that factors for DNA double-stranded break repair and microhomology-mediated end-joining (MMEJ), such as H2ax, Fen1, DNA polymerase Polθ, Cdk1, and Plk1, exhibited a step-wise increase and Mdc1 a decrease in expression in MmuPV1-infected tissues and MmuPV1 tumors relative to normal tissues. Increased expression of mitotic kinases CDK1 and PLK1 appears to be correlated with CtIP phosphorylation in MmuPV1 tumors, suggesting a role for MMEJ-mediated DNA joining in the MmuPV1 integration events that are associated with MmuPV1-induced progression of tumors.